1981
DOI: 10.3758/bf03207361
|View full text |Cite
|
Sign up to set email alerts
|

Simple and contingent aftereffects of perceived duration in vision and audition

Abstract: After repeated presentations of a long inspection tone (800 or 1,000 msec), a test tone of intermediate duration (600 msec) appeared shorter than it would otherwise appear. A short inspection tone (200 or 400 msec) tended to increase the apparent length of the intermediate test tone. Thus, a negative aftereffect of perceived auditory duration occurred, and a similar aftereffect occurred in the visual modality. These aftereffects, each involving a single sensory dimension, are simple aftereffects. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
69
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 27 publications
11
69
2
Order By: Relevance
“…Similar results have been reported by studies investigating the effect of trial history on duration judgments (Becker & Rasmussen, 2007;Walker, Irion, & Gordon, 1981). These studies also show that presentation of a particular duration causes the perception of http://dx.doi.org/10.1016/j.visres.2016.11.003 0042-6989/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar results have been reported by studies investigating the effect of trial history on duration judgments (Becker & Rasmussen, 2007;Walker, Irion, & Gordon, 1981). These studies also show that presentation of a particular duration causes the perception of http://dx.doi.org/10.1016/j.visres.2016.11.003 0042-6989/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionsupporting
confidence: 73%
“…However, behavioral studies have shown that trial history effects and the duration after-effect do not show any selectivity to low-level visual features such as orientation (Li, Yuan, & Huang, 2015;Walker et al, 1981), arguing against a role of early visual cortex in channel based duration processing. Furthermore, many other different brain areas have been implicated in duration processing, providing alternative possible neural loci for the channel based encoding of duration (Hayashi et al, 2015;Ivry & Schlerf, 2008;Mauk & Buonomano, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that transition duration, and not rate, provides the primary temporal cue to the stop-continuant contrast (Schwab, Sawusch, & Nusbaum, 1981), so it seems reasonable that preceding temporal information would affect the distinction by means of durational contrast (e.g., Goldstone et al, 1959;Goldstone et al, 1957;Walker & Irion, 1979;Walker et al, 1981). However, the precursor sequences in the experiments described here varied in both the duration and presentation rate of tones, creating a possible confound in this respect.…”
Section: Discussionmentioning
confidence: 67%
“…Along these lines, Diehl and Walsh (1989) assert that apparent speaking rate effects may result from durational contrast whereby temporal cues, such as the length of an acoustic segment, are perceived relative to nearby segments rather than absolutely. Thus, for example, listeners may accept longer formant transitions for [b] at slower speaking rates not because they reveal something about typical articulation, but simply because they appear shorter than longer surrounding segments, a pattern previously documented for nonspeech tone durations (Goldstone, Boardman, & Lhamon, 1959;Goldstone, Lhamon, & Boardman, 1957;Walker & Irion, 1979;Walker, Irion, & Gordon, 1981). Oller, Eilers, Miskiel, Burns, and Urbano (1991) speculated further on the precise workings of a durational contrast effect.…”
mentioning
confidence: 99%